Bieberback functions and periodic distributions - V. Karunakaran (International Journal of Mathematics and Mathematical Sciences)
This paper deals with a correspondence between the periodic distributions and holomorphic functions. Periodic distributions whose “negative” Fourier coefficients are zero are characterised as the boundary values of certain holomorphic functions.